FREQUENCY OF MECKEL’S DIVERTICULUM IN ACUTE APPENDICITIS (Journal of Medical & Health Sciences Review, 2025)
Meckel’s diverticulum (MD) is the most common congenital anomaly of the gastrointestinal tract. Its incidence is increasing in the general population. Moreover, contemplation about the need to remove an incidentally discovered Meckel's diverticulum continues. To determine the frequency of Meckel’s diverticulum in patients undergoing acute appendectomy. A cross-sectional study was conducted at the Department of Surgery, Jinnah Postgraduate Medical Center, Karachi.  All patients aged 18 to 50 years of either gender who presented with acute appendicitis were enrolled in this study. Meckel’s diverticulum was explored during surgery, and the Presence of a blind segment 3–6 cm long in the distal ileum, within 60–100 cm of the ileocecal valve, was considered as Meckel's diverticulum. The mean age of the patients was 31.19±10.17 years. The mean BMI of the patients was 28.60/m2±1.50Kg/m2. There were 385 (27.80%) females and 1001 (72.20%) males. Obesity was found in 18 (14.30%) patients. In our study frequency of Meckel’s diverticulum was found in 11 (0.79%) acute appendectomy patients.